Case Report: Non-episodic Angioedema With Eosinophilia in a Young Lactating Woman - Hirmatsu-Ito, Mizuho; Nakamura, Nobuhisa; Miyabe, Megumi; Matsubara, Tatsuaki; Naruse, Keiko (Frontiers in Immunology, 2021)
Angioedema with eosinophilia has two different trends: episodic angioedema with eosinophilia (EAE), known as Gleich’s syndrome, and non-episodic angioedema with eosinophilia (NEAE). We present the case of a young lactating woman with non-episodic angioedema. She had no history of parasitic or nonparasitic infections. Physical examination showed striking, non-pitting edema of both lower extremities. Her weight had not changed significantly throughout the course of illness. She showed no other symptoms, and her vital signs were normal. There was no evidence of anemia, hypoalbuminemia, thyroid dysfunction, heart failure, renal failure, or postpartum cardiomyopathy. Based on these findings, we diagnosed her with angioedema with eosinophilia. Given the scarcity of information about this condition, we embarked upon exploring the dynamics between cytokines/chemokines and edema in this patient. We successfully quantified the edema by bioimpedance analysis. In addition, we revealed the involvement of interleukin-5 (IL-5), thymus-and activation-regulated chemokine/C-C motif chemokine ligand-17 (TARC/CCL-17), Eotaxin-3/CCL-26, tumor necrosis factor-α (TNF-α), vascular endothelial growth factor (VEGF), monocyte chemotactic protein-4/CCL-13 (MCP-4/CCL-13), eotaxin-1/CCL-11, and regulated on activation, normal T expressed and secreted/CCL-5 (RANTES/CCL-5) in NEAE. Lastly, we elucidated the strong relationship between these parameters. To the best of our knowledge, this is the first such study of its kind.